The language of sycamores eaudiobook - Wingate, Lisa (Tending Roses, 2019)
Karen Sommerfield has been hiding from life-immersing herself in a high-powered job-until the day the company downsizes her out of a job and the doctor tells her that she may have cancer. It's a double blow that sends Karen on a search for herself in the last place she ever thought to look: Grandma Rose's old farm. As Karen's hectic schedule falls away, she opens up to the unexpected. In the quiet of the Missouri Ozarks, she hears the soft, secret language of the sycamore trees, and discovers answers and a joy to make her life complete.